Cross-cultural Adaptation, Internal Consistency and Validity of the Handwriting Proficiency Screening Questionnaire (HPSQ) for Spanish Primary School-age Children - Cantero-Téllez, Raquel; Medina-Porqueres, Iván; Piñel, Inmaculada; García-Orza, Javier (OMICS International Pvt Ltd, 2015)
Aim: To translate and culturally adapt the HPSQ into Spanish and to obtain a reliable and viable version. Additionally, the psychometric properties of this new version, namely, the internal consistency and validity, were evaluated using a sample of 165 Spanish school-children. Methods: The sequence of this process was as follows: forward translation, synthesis, back-translation, expert committee review and pilot study. In forward and backward translation items were easy to translate and problems with cross-cultural adaptation were not found. Content validity was evaluated by using item-objective congruence (IOC) value. Internal consistency of the Spanish version was measured with Cronbach’s alpha coefficient; whereas principal-component factor analyses were used to explore construct validity. Results: The Spanish version of the HPSQ retains the characteristics of the English original, high internal consistency (Cronbach alpha value of 0.78) and good construct and content validity (IOC values above 0.7). Conclusion: The results indicate that the Spanish version of HPSQ is a reliable and valid instrument for handwriting evaluation in Spanish school-age children.
Keywords: Psicometría - Test; Psychometric testing; School performance; Handwriting; Prehension; Phonographic knowledge